A model of anaerobic digestion for biogas production using abel equations (2017)
Mathematical models for biogas production are studied due to their importance in the use of control and optimization of renewable resources and clean energy. In this paper, we combine two algebraic methods to obtain solutions of Abel equation of first kind that arises from a mathematical model to biogas production formulated in France on 2001. The aim of this paper is to obtain Liouvillian solutions of Abel’s equations through Hamiltonian algebrization. As an illustration, we present graphics of solutions for Abel equations and solutions for Abel equations in algebraic form.